Adipose triglyceride lipase promotes the proliferation of colorectal cancer cells via enhancing the lipolytic pathway. Issue 8 (23rd February 2021) - Yin, Haofan; Li, Wentao; Mo, Laiming; Deng, Shaotuan; Lin, Weijia; Ma, Caiqi; Luo, Zhaofan; Luo, Chuanghua; Hong, Honghai
Abstract: Abnormal lipid metabolism is the sign of tumour cells. Previous researches have revealed that the lipolytic pathway may contribute to the progression of colorectal cancer (CRC). However, adipose triglyceride lipase (ATGL) role in CRC cells remains unclear. Here, we find that elevated ATGL positively correlates with CRC clinical stages and negatively associates with overall survival. Overexpression of ATGL significantly promotes CRC cell proliferation, while knockdown of ATGL inhibits the proliferation and promotes the apoptosis of CRC cells in vitro. Moreover, in vivo experiments, ATGL promotes the growth of CRC cells. Mechanistically, ATGL enhances the carcinogenic function of CRC cells via promoting sphingolipid metabolism and CoA biosynthesis pathway‐related gene levels by degrading triglycerides, which provides adequate nutrition for the progression of CRC. Our researches clarify for the first time that ATGL is a novel oncogene in CRC and may provide an important prognostic factor and therapeutic target for CRC.